Work-Life Balance, Motivation, and Employee Well-Being in Integrated Resorts: A Narrative Literature Review - Duyagit, Ronel; Delos Reyes, Kim; Enanod, Jennifer; De Vera, Raymel (JPAIR Multidisciplinary Research, 2026)
The hospitality and gaming industry presents persistent challenges to employee well-being due to irregular schedules, emotional labor, and continuous customer demands. This study examines the relationships among work-life balance (WLB), motivation, and personal impact (PI) within the context of Solaire Resort North, a luxury integrated resort in the Philippines. A qualitative narrative literature review was conducted, guided by the Job Demands-Resources (JD-R) model and Self-Determination Theory (SDT). Thematic analysis was applied to selected global and local studies. Findings confirm that WLB functions as a critical job resource that enhances intrinsic motivation by satisfying autonomy and relatedness needs. However, both WLB and motivation fail to buffer the negative effects of chronic job demands on PI, leading to motivational self-exploitation and heightened personal strain. The study contributes new insight to JD-R literature by highlighting the decoupling of internal states and external well-being outcomes. Organizational reforms—flexible scheduling, wellness programs, and family-supportive policies—are recommended to mitigate personal costs and sustain workforce resilience in high-demand service environments.
Keywords: Human Resource Management; Motivation; Narrative Literature Review; Philippines; Work-Life Balance